Nutrient demand modeling of a soilless cucumber crop under greenhouses conditions in a humid tropical climate. Issue 20 (13th November 2018) - Salcedo, Galo Alberto; García-Caparrós, Pedro; Pérez-Saiz, Mónica; Reca, Juan; Lao, María Teresa
ABSTRACT: This experiment was conducted in a greenhouse in Vinces Los Rios (Ecuador). The aim of this work is to evaluate the relationship between different parameters and the nutrient demand of a greenhouse soilless cucumber production system in a tropical climate as well as to propose an empirical model for the design of the nutrient supply to the system. Considering the results obtained in this experiment, there was a high correlation between nutrient demands of the system with nutrient supplies and water uptake but not with leaf area index. With respect to the models, nutrient supplies and leaf area index were the most significant variables for nitrate (NO3 − ), chloride (Cl − ) and manganese (Mn). For calcium (Ca 2+ ), magnesium (Mg 2+ ) and zinc (Zn), nutrients supply was the most significant variable and for the rest of nutrients [phosphates (H2 PO4 − ), sulfates (SO4 2 ) −, potassium (K + ), sodium (Na + ) and iron (Fe)], the three variables assessed were significant.